Pengaruh Penerapan Pembelajaran Model Ryleac Berbantuan PhET Terhadap Keterampilan Proses Sains Siswa - Tirtawaty Abdjul; Nancy Katili; Septiana Kurniasari; Muhammad Yunus (Postgraduate, University of Mataram, 2022)
This study aims to determine the effect of applying the PhET-assisted Ryleac model of science learning tools on students' science process skills. The research method is a quasi-experimental design with a one-group pretest-posttest research design. The location of this research is at Junior High School, SMP Negeri Tangagah, in class VIII, Bolaang Uki District, Bolaang Mongondow Selatan Regency, in the 2021/2022 Academic Year. The sample in this study were students of class VIII types A and B. The researcher first validated the Ryleac model of science learning tools assisted by PhET by expert validators and obtained the overall results that the learning tools were very valid. The results of this study indicate that applying the Ryleac model of science learning tools assisted by PhET in learning can improve students' science process skills because students' learning activities are excellent during the learning process. Observation of students' science process skills during the learning process showed excellent results. All students' average responses positively responded to PhET-assisted Ryleac learning with an excellent category. The test results for science process skills showed that PhET-assisted Ryleac model learning could improve students' science process skills